Exergy analysis of solar energy applications - Saidur, Rahman; BoroumandJazi, G.; Mekhilef, Saad; Jameel, Mohammed (Elsevier, 2012)
Solar energy is a clean, abundant and easily available renewable energy. Usage of solar energy in different kinds of systems provides scope for several studies on exergy analysis. In the present work, a comprehensive literature review has been carried out on exergy analysis of various solar energy systems. The systems considered under study are solar photovoltaic, solar heating devices, solar water desalination system, solar air conditioning and refrigerators, solar drying process and solar power generation. The summary of exergy analysis and exergetic efficiencies is presented along with the exergy destruction sources.